STRATEGY IN MANAGING STUNTING THROUGH MONITORING OF CONSUMPTION PATTERNS OF PREGNANT WOMEN IN GAMPONG TEUPIN PANAH, KAWAY XVI DISTRICT, WEST ACEH - Noni Amelia; Tengku Nih Farisni (RADJA PUBLIKA, 2022)
Stunting is a nutritionary disputed point accompanying to the aggrandizement and exploitation of toddlers. The determination of this contemplate is to supply a resolution for the agreement in tackling stunting nailed down monitoring the consumption archetypes of heavy with child women in Teupin Panah Village, Kaway XVI District. This evaluation was conducted victimisationing descriptive qualitative evaluation in marchland 2022 at the Posyandu Gampong Teupin Arrow, Kaway XVI District, westbound Aceh Regency. fountain-heads of collections in this contemplate victimisationing influential collections and less important collections with the character of heavy with child women as severals as 10 people. The consequences of press conference conducted in Teupin Panah Village, Kaway XVI District, explicit that thither were all the more heavy with child women in the community who did not distinguish the grandness of consumption archetypes during pregnancy, As it is recognized that consumption life-giving chop chop during gestation conspicuously lay hold of the aggrandizement and exploitation of the descendant in the womb. The determination is that a heavy with child womanhood be in want of to remuneration consideration to the aspiration of nutrients that participate her dead end for that it grips a diversification of nutritionary aspiration to accommodate the nutrients contained in the chop chop exhausted by heavy with child women.